Women as stewards of environmental and social transformations in tropical forests - Rogelja, Todora; Kroese, Luca; Bulkan, Janette; Elias, Marlene; Monterroso, Iliana; Öllerer, Barbara; Wallin, Ida (2025)
Women are driving transformative change across the tropics, yet their critical roles in forest management, conservation and resource use often remain unrecognized. From gathering non-timber forest products (NTFPs) to safeguarding sacred groves and leading community initiatives, women’s contributions are essential to the social and ecological fabric of forest-dependent communities. However, their access to resources and decision-making power remains limited. By discussing the essential roles that women play as environmental stewards, the articles in this edition of Tropical Forest Issues present the significant impacts that women can have on shaping the future of tropical forest landscapes.